1995
DOI: 10.1128/jvi.69.3.1575-1581.1995
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus-encoded nonstructural protein NS4A has versatile functions in viral protein processing

Abstract: A transient protein expression system in COS-1 cells was used to study the role of hepatitis C virus (HCV)-encoded NS4A protein on HCV nonstructural polyprotein processing. By analyzing the protein expression and processing of a deletion mutant polypeptide, NS⌬4A, which encodes the entire putative HCV nonstructural polyprotein except the region encoding NS4A, the versatile functions of NS4A were revealed. Most of the NS3 processed from NS⌬4A was localized in the cytosol fraction and was degraded promptly. Copr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
126
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(133 citation statements)
references
References 23 publications
6
126
0
1
Order By: Relevance
“…4B). These results show concordance with those of previous studies (14,16,50). The sodium carbonate wash data indicated that NS4B integrated less efficiently in the microsomal membranes than our control protein, Lep (a known integral protein) (17), despite the clear ER localization of NS4B shown above by microscopy.…”
Section: Resultssupporting
confidence: 93%
“…4B). These results show concordance with those of previous studies (14,16,50). The sodium carbonate wash data indicated that NS4B integrated less efficiently in the microsomal membranes than our control protein, Lep (a known integral protein) (17), despite the clear ER localization of NS4B shown above by microscopy.…”
Section: Resultssupporting
confidence: 93%
“…However, the soluble protease/helicase NS3 protein associates with the membrane by interaction with NS4A, a cofactor of the protease domain of NS3. NS4A is a 54-amino acid cofactor for both serine protease and helicase activities of NS3, and its cofactor activity requires stable complex formation between NS3 and NS4A, an interaction that also stabilizes NS3 (Bartenschlager et al, 1995;Pang et al, 2002;Tanji et al, 1995). NS3 is found in association with ER or ER-like membranes when coexpressed with NS4A, but it is distributed diVusely throughout the cytoplasm and nucleus when expressed in the absence of NS4A (Wolk et al, 2000).…”
Section: A Viral Replication Associated With Membranes Derived From mentioning
confidence: 99%
“…For instance, this domain can unwind double-stranded RNA and DNA in vitro [36], but direct evidence is lacking that it binds to or unwinds viral RNA during the replication cycle in vivo. The small NS4A protein binds to NS3, acts as a cofactor for both NS3 activities [28,37], and anchors the NS3-4A heterodimer in the membrane [38]. NS4B is a polytopic membrane protein that can oligomerize and may serve as a scaffold for replicase assembly [39,40].…”
Section: Introductionmentioning
confidence: 99%